Menghindari Tindakan Bullying di SD Plus Al-Muhajirin Purwakarta - Neneng Sri Wulan; Anisa Fitriani; Juliati Ningsih; Maria Khofifah Rhamadan; Vena Elvana (Jurnal Informasi Pengabdian Masyarakat, 2023)
Bullying/bullying is unpleasant behavior both verbally, physically, or socially in the real world and in cyberspace that makes a person feel uncomfortable, hurt and even pressured, whether done by individuals or groups (Sri Wahyuningsih, 2021). This study aims to analyze bullying behavior and the teacher's role in dealing with bullying behavior among students towards the formation of student character. This negative behavior is most likely done because they have been the victim of bullying from someone more powerful, for example a parent, sibling, senior or peer. Factors that cause bullying can be divided into 2 causes, namely internal and external causes. Internal causes are personality characteristics, past violence, and parental attitudes while external causes are the social and cultural environment. Bullying can be prevented from an early age, because bullying is not something that can only be done by adults, but can be done by all ages, therefore it can be prevented as early as possible. And because of that students carry out socialization of acts of bullying in elementary schools in fostering a sense of concern for fellow peers for elementary students.